Effectiveness of policy development and implementation of L1-based multilingual education in Cambodia. Issue 2 (17th February 2019) - Benson, Carol; Wong, Kevin M.
ABSTRACT: This article presents the current state of ongoing research on policy development and implementation of first language-based multilingual education in five northeastern provinces of Cambodia that are home to significant ethnolinguistic minority populations. This research, supported by CARE Cambodia in collaboration with the Ministry of Education, Youth and Sport, qualitatively investigates policy development and structural support for MLE implementation and analyzes learner achievement data. Pulling together the findings, we highlight lessons learned throughout the process about creating the conditions for MLE success and about assessing MLE student outcomes that could inform MLE policy and practice in similar low-income contexts and have important implications for quality and equity in educational development.